Modern India and Dietary Calcium Deficiency—Half a Century Nutrition Data—Retrospect–Introspect and the Road Ahead - Harinarayan, Chittari Venkata; Akhila, Harinarayan; Shanthisree, Edara (Frontiers in Endocrinology, 2021)
Calcium and vitamin D are inseparable nutrients required for bone health. In the past half a century, the dietary calcium intake of rural, tribal, and urban India has declined. Though India is the largest producer of milk and cereals, the major source of calcium in India is through non-dairy products. The highest intake of cereals and lowest intake of milk & milk products was observed in rural and tribal subjects whereas, the intake of cereals, milk & milk products were similar in both urban and metropolitan subjects. One of the reasons for lower calcium intake was the proportion of calcium derived from dairy sources. Over the past half a century, the average 30-day consumption of cereals in the rural and urban population has declined by 30%. The Per Capita Cereal Consumption (PCCC)has declined despite sustained raise in Monthly Per capita Consumption Expenditure (MPCE) in both rural and urban households. The cereal consumption was the highest in the lowest income group, despite spending smaller portion of their income, as cereals were supplied through public distribution system (PDS). About 85% of the Indian population are vitamin D deficient despite abundant sunlight. Dietary calcium deficiency can cause secondary vitamin D deficiency. Though India as a nation is the largest producer of milk, there is profound shortage of calcium intake in the diet with all negative consequences on bone health. There is a decline in dietary calcium in the background of upward revision of RDI/RDA. There is a gap in the production-consumption-supply chain with respect to dietary calcium. To achieve a strong bone health across India, it is imperative to have population based strategies addressing different segments including supplementing dietary/supplemental calcium in ICDS, mid-day-meals scheme, public distribution system, educational strategies. Other measures like mass food fortification, biofortification, bioaddition, leveraging digital technologies, investments from corporate sector are some measures which can address this problem. India is a vast country with diverse social, cultural and dietary habits. No single measure can address this problem and requires a multi-pronged strategic approach to tackle the dietary calcium deficiency to achieve strong bone health while solving the problem of nutritional deficiency.